New insights into the Upper Pleistocene directed blast eruption, Popocatépetl volcano, México - Lira-Beltrán, R. Marcela (2024)
Volcanic eruptions of the directed blast type are characterized by powerful explosions with a significant lateral pyroclastic density current (PDC) component that can travel at speeds above 100 m s–1 and affect hundreds of square kilometers around a volcano. This study presents preliminary results of a detailed fieldwork and stratigraphic study of deposits associated with the Ocoxaltepec Blast deposit, which originated from the Popocatépetl volcano during a strong eruption associated with the southwestward sector collapse of the volcanic edifice around 23,500 ka BP. Within the study area, which contains 58,870 inhabitants, we found 42 new sites where the blast deposit outcrops, in locations up to 25 km from the volcano crater, with thicknesses up to over 20 m. We divide these blast deposits into two categories: confined channel-fill PDC deposits and unconfined interfluve and upland PDC deposits. With the new data we have estimated the dispersion area of the directed blast to be approximately 338 km2. Twenty-nine of the new outcrops are located outside the hazard polygon associated with concentrated PDCs related to the lowest probability Plinian eruption currently considered from Popocatépetl.